57 Percutaneous transfemoral treatment of LVOT pseudoaneurysms following bioprosthetic AVR. (30th September 2020) - Brennan, PF; Nzewi, O; Spence, MS; Owens, C
Abstract : Introduction: Surgical aortic valve replacement (AVR) is the intervention of choice for many patients with aortic valve disease. Left ventricular outflow tract (LVOT) pseudo-aneurysm is a rare complication after AVR but, importantly, can present incidentally in the absence of specific symptoms. With progression the pseudo-aneurysm can be complicated by potentially fatal consequences including tract thrombosis, fistula formation, pseudo-aneurysmal rupture and compression of surrounding structures e.g. the coronary arteries. Methods: We report two cases of LVOT pseudo-aneurysm following SAVR, the various diagnostic/treatment-planning imaging modalities used, and the subsequent successful percutaneous interventions applied. Results: The first patient is a 69-year-old female who underwent elective SAVR with a 25 mm Trifecta prosthesis. She had a history of bicuspid aortic valve disease (figure 1a ). After an uncomplicated surgical course, she attended for a routine outpatient transthoracic echocardiogram (TTE). At this stage she was asymptomatic. An anechoic space was identified 15 mm adjacent to the AVR, in the non-coronary cusp position. There was evidence of bidirectional flow within the space. She was admitted to hospital and a TEE was performed which confirmed a 15 mm × 27 mm echo free space adjacent to the aortic root (figure 1b ) and colour doppler flow mapping demonstrated continuity of this space with the LVOT (figure 1c ). Cardiac CT confirmed the presence of an LVOT pseudoaneurysm (figure 1d ). The second patient is 76-year-old female who underwent elective SAVR with a 19 mm Trifecta prosthesis for severe trileaflet aortic stenosis. She was readmitted, 2-months later, with chest pain and dyspnoea. Due to concerns regarding an acute aortic syndrome a CT aorta was performed which suggested an LVOT pseudo-aneurysm arising in the immediate infra-annular vicinity. Subsequent TEE and cardiac-gated CT confirmed a 4 × 9 × 41 mm complex pseudo-aneurysm. Both patients were discussed with the heart team and the consensus was re-operation carried significant risk and to proceed to transfemoral percutaneous closure. The pseudo-aneurysms were easily visible during fluoroscopic angiography in the cathlab (figure 2a ) and were both cannulated with guide extension catheters (figure 2b ). Under general anaesthesia with TEE guidance both pseudoaneurysms were successfully using a single AVP2 10 mm closure device (figure 2c ). Repeat CT at 3 months revealed successful closure and placement of the devices (figure 2d ) for each patient. At most recent follow-up they both remain asymptomatic, admission-free and have normal bioprosthetic valve function. Table 1 is a summary of both cases. Conclusion: LVOT pseudoaneurysms, a rare complication of SAVR, can be successfully treated percutaneously. In an era of evolving percutaneous structural heart interventions it is highly important that we possess a thorough understanding of the many percutaneous devices and treatment options available for post-surgical complications.